2019
DOI: 10.1186/s12879-019-4303-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the serum Aspergillus-specific IgG, IgA and IgM assays for chronic pulmonary aspergillosis diagnosis

Abstract: Background Chronic pulmonary aspergillosis (CPA) is an underdiagnosed and misdiagnosed disease and now increasingly recognised. However, the diagnosis of CPA remains challenging. In this study, we aimed to investigate the diagnostic values of serum Aspergillus -specific IgG, IgA and IgM antibodies in patients with CPA. Methods The prospective study was performed at Chinese People’s Liberation Army General Hospital in Beijing, from January 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…In the current guidelines, the detection of serum Aspergillus precipitin IgG antibody is a key diagnostic criterion for CPA [1,24]. Unfortunately, it is unclear whether the presence of Aspergillus IgG antibody could also be a supportive finding in the diagnosis of Aspergillus nodules.…”
Section: Discussionmentioning
confidence: 99%
“…In the current guidelines, the detection of serum Aspergillus precipitin IgG antibody is a key diagnostic criterion for CPA [1,24]. Unfortunately, it is unclear whether the presence of Aspergillus IgG antibody could also be a supportive finding in the diagnosis of Aspergillus nodules.…”
Section: Discussionmentioning
confidence: 99%
“…The LFA detects GM and is licensed for serum and BAL, crossreactivity with various fungal genera exists [24], see Table 1. Head to head comparison of LFD and LFA from BALs showed identical specificity, with sensitivity and negative predictive values slightly being better for LFA [26], for more information see [30]. However, this process is slow and takes weeks to months even in improved patients; a lack of decline is suspicious of treatment failure [19].…”
Section: Resultsmentioning
confidence: 94%
“…The characteristics of included studies are shown in Tables 1 and 2 below 5–11,17‐42 . Participants' characteristics varied greatly across the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the diagnostic values of Aspergillus IgA and IgM antibodies remain unclear. Since the publication of the two guidelines, 2,3 several primary studies have been published on the diagnostic test accuracy of IgA and IgM antibodies for CPA 5–9 . Moreover, a new test for the diagnosis of CPA, IgG + IgM antibody, has recently been reported 10,11 …”
Section: Introductionmentioning
confidence: 99%